Aggression in borderline personality disorder - Látalová, K; Prasko, J (The Psychiatric quarterly, 2010)
This review examined aggressive behavior in Borderline Personality Disorder (BPD) and its management in adults. Aggression against self or against others is a core component of BPD. Impulsiveness is a clinical hallmark (as well as a DSM-IV-TR diagnostic criterion) of BPD, and aggressive acts by BPD patients are largely of the impulsive type. BPD has high comorbidity rates with substance use disorders, Bipolar Disorder, and Antisocial Personality Disorder; these conditions further elevate the risk for violence. Treatment of BDP includes psychodynamic, cognitive behavioral, schema therapy, dialectic behavioral, group and pharmacological interventions. Recent studies indicate that many medications, particularly atypical antipsychotics and anticonvulsants, may reduce impulsivity, affective lability as well as irritability and aggressive behavior. But there is still a lack of large, double blind, placebo controlled studies in this area.
Keywords: Psychotherapy; agrese; hraniční porucha osobnosti; Humans; farmakoterapie; lidé; psychoterapie; Aggression; Borderline Personality Disorder; Drug Therapy